PENEKANAN NABATI PADA TANAH TANAMAN TOMAT TERKONTAMINASI Fusarium oxysporum F.SP. lycopersici - Andri Sugito; Heru Adi Djatmiko; Loekas Soesanto (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2010)
[BOTANICAL SUPPRESSION ON CONTAMINATED TOMATO SOIL BY Fusarium oxysporum f.sp. lycopersici]. A screen house study was carried out to identify the best botanical materials and their application time on suppression of Fusarium oxysporum f.sp. lycopersici pathogen in contaminated soil and on the growth of tomato. A randomized block design with three replications was used allocate 19 treatment combinations of botanical materials (extract of neem leaves, clove leaves, teak bark, pine bark, and catalpha leaves) and time of applications (4, 2, or  4 and 2 weeks before planting).  Observations were made on the development of the pathogen, disease intensity, and plant growth. Results showed that all botanical materials used could reduce the pathogen population but not the plant growth components. Extract of clove leaves applied at 4 weeks before planting was the best in decreasing the pathogen population (79.22 %).